Mucoadhesive chitosan-coated Fe3O4 magnetic nanoparticles for the treatment of intestinal dysmotility - Signorello, Paolo; Cacopardo, Ludovica; Fontana, Francesco; Martins, Cláudia; Sarmento, Bruno; Ahluwalia, Arti (Frontiers in Nanotechnology, 2026)
Intestinal dysmotility represents a significant health burden, often leading to severe and life-threatening complications. Current therapies are limited, highlighting the need for smart treatment strategies. We propose a novel, minimally invasive approach involving the oral delivery of mucoadhesive magneto-responsive nanoparticles, which can be actuated by external magnets. As a proof of concept, Fe3O4 nanoparticles were coated with chitosan to optimise their interaction and adhesion to the intestinal epithelium and to enhance cytocompatibility. To protect the chitosan-coated particles from the acidic conditions of the stomach and enable their targeted release further along the gastrointestinal tract, they were encapsulated in pH responsive alginate beads. Using an advanced 3D multi-layered in vitro model of the intestinal wall, we confirmed the absence of nanoparticle translocation across the barrier. Moreover, epithelial para- and transcellular transport pathways were unaltered in the presence of the chitosan-coated particles, suggesting that nutrient passage is conserved. Finally, a hydrogel simulating the intestinal submucosal layer was loaded with the nanoparticles and then actuated with external magnets to verify their capacity to generate physiological strains. These findings demonstrate the feasibility of magnetically actuated mucoadhesive nanoparticles as a foundation for new therapeutic strategies to restore intestinal motility, paving the way for externally controlled, minimally invasive interventions in gastrointestinal disorders.